PENGEMBANGAN PERANGKAT PEMBELAJARAN SAINS SMP BERORIENTASI PADA PENDEKATAN SAINS TEKNOLOGI MASYARAKAT UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF - Hunaepi Hunaepi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
The availability of science learning instructional that integrate between the science, society and technology is still very limited so that it needs to be developed science-learning instructional with science, society and technology oriented. This learning instructional development aims to develop science learning instructional with science, technology and society approach oriented to improve students' cognitive abilities. Learning instructional that have been developed in trials in class VIIb with a number of 30 students at State Yunior High School 2 Sepulu Madura through One Group Pretest-Postest Design. Instructional development uses the Kemp development model. The results showed that RPP validation, student textbooks, Student Worksheets, and category rating sheets were feasible with validity of instrument reliability of RPP 91%; Student book 90%; Student Worksheet 92%. The highest teacher activity is to guide the experiment by 22% at meeting one (P1) and at the second meeting (P2) 24%. Highest student activity is Observing with 22% (P1) and 24%  (P2). Lesson learned on (P1 and P2) is implemented (92%) and (75%). Student responses to the instructional and learning are good categorized or students respond positively. Cognitive abilities seen from the completeness of Pretest learning indicators averaged <60 categorized incomplete, Postest average ≥ 60 categorized complete, individual completeness on average Pretest <60 categories incomplete, Postest average ≥ 65 category of completeness, and mastery classically on Pretest <75 is categorized incomplete, whereas in Postest ≥ 75 is complete. The conclusion of the research shows that the approach of Science, Techonology, and Society on damage and environmental pollution subject material in State Junior High School 2 Sepulu can improve students' cognitive abilities and learning instructional used in this research categorized as valid and reliable.